2014
DOI: 10.1016/j.ijdevneu.2014.06.009
|View full text |Cite
|
Sign up to set email alerts
|

Polyols accumulated in ribose‐5‐phosphate isomerase deficiency increase mitochondrial superoxide production and improve antioxidant defenses in rats' prefrontal cortex

Abstract: The ribose-5-phosphate isomerase deficiency is an inherited condition, which results in cerebral d-arabitol and ribitol accumulation. Patients present leukoencephalopathy, mental retardation, and psychomotor impairment. Considering that the pathophysiology of this disorder is still unclear, and literature are sparse and contradictory, reporting pro and antioxidant activities of polyols, the main objective of this study was to investigate some parameters of oxidative homeostasis of prefrontal cortex of rats inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 28 publications
1
4
0
Order By: Relevance
“…Another interesting finding of our study is that ribitol treatment, again in contrast to ribose treatment, significantly increases levels of reduced glutathione (GSH). This result is in agreement with an early report by Stone et al in 2014 [ 35 ]. The previous study aimed to assess the roles of polyols, specifically arabitol and ribitol, in the pathophysiology of a disease caused by ribose-5-phosphate isomerase deficiency [ 36 ].…”
Section: Discussionsupporting
confidence: 94%
“…Another interesting finding of our study is that ribitol treatment, again in contrast to ribose treatment, significantly increases levels of reduced glutathione (GSH). This result is in agreement with an early report by Stone et al in 2014 [ 35 ]. The previous study aimed to assess the roles of polyols, specifically arabitol and ribitol, in the pathophysiology of a disease caused by ribose-5-phosphate isomerase deficiency [ 36 ].…”
Section: Discussionsupporting
confidence: 94%
“…Nevertheless, it was observed that ribitol facilitated a rise in the glutathione peroxidase, catalase, and superoxide dismutase activity. This effect is likely a result of an augmented generation of the superoxide radical [55].…”
Section: Discussionmentioning
confidence: 99%
“…The latter is based on the decreased striatal levels of mainly ribitol and pyroglutamic acid. Ribitol has been shown to increase oxidative stress/ROS production [ 37 ] and can be used to indicate cellular oxidative stress levels. Furthermore, pyroglutamic acid is an intermediate in glutathione metabolism, produced when glutathione is broken down (i.e., oxidized by ROS).…”
Section: Discussionmentioning
confidence: 99%